THE DEVELOPMENT OF THE STRATEGIC LEADERSHIP COMPONENTS AND INDICATORS OF ISLAMIC PRIVATE SCHOOLS’ ADMINISTRATORS IN THE THREE SOUTHERN BORDER PROVINCES OF THAILAND - Basel Abdulwahab; Sinchai Suwanmanee; Rungchatchadaporn Vehachart; Suntaree Wannapairo (Universitas Islam Negeri Alauddin Makassar, 2022)
The objective of this research was to study the Strategic Leadership Components and Indicators of Islamic Private Schools’ administrators in the Three Southern Border Provinces. The research process in phase 1 consists of 5 steps: step 1 was the Strategic Leadership Components and Indicators from related documents and research, step 2 was the synthesis of the Strategic Leadership Components and Indicators, step 3 was preparing the questionnaire to group the indicators in accordance with the Competency Framework from 5 qualified persons, step 4 was preparing the questionnaire to group the key indicators of leadership in accordance with Islamic principles from 10 qualified persons, and step 5 was preparing the agreeing-disagreeing questionnaire on the Strategic Leadership Indicators from 23 qualified persons. The research in phase 2 was developing Strategic Leadership Indicators, using 2 rounds of Fucus Group Discussion technique. The results of the research showed that the Strategic Leadership Components consists of 5 components: 1) Organizational Direction Establishment, 2) Strategic Formulation, 3) Strategic Implementation, 4) Strategic Control and Evaluation, and 5) High Level Thinking Process, the Strategic Leadership Indicators consists of 166 indicators, and the development of strategic leadership indicators agreed from Focus Group Discussion techniques in round 1 from 7 qualified persons and in round 2 from 11 qualified persons consists of 110 indicators.